лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля лялляляляляллляляля
=19/48
Объяснение:
12a^2-2ax-7a+7x=
=12a(a-x)-7(a-x)=
=(a-x)(12x-7)
Підставляємо:
(1 1/16-2/3)(12*2/3-7)=
=(17/16-2/3)(8-7)=
=(19/48)(1)=
=19/48